Exposition of traditional Malay house architectural design element influencing influencing indoor performance / Nik Siti Fatimah Nik Hassin and Alamah Misni - Nik Hassin, Nik Siti Fatimah; Misni, Alamah (College of Built Environment, 2023)
Traditional Malay houses (TMH) practicing climatic design strategies are acknowledged to have more acceptable thermal performance than modern residential houses.